Predicting Individual Variation in Language From Infant Speech Perception Measures. Issue 4 (9th December 2013) - Cristia, Alejandrina; Seidl, Amanda; Junge, Caroline; Soderstrom, Melanie; Hagoort, Peter
<x xml:space="preserve">Abstract</x> There are increasing reports that individual variation in behavioral and neurophysiological measures of infant speech processing predicts later language outcomes, and specifically concurrent or subsequent vocabulary size. If such findings are held up under scrutiny, they could both illuminate theoretical models of language development and contribute to the prediction of communicative disorders. A qualitative, systematic review of this emergent literature illustrated the variety of approaches that have been used and highlighted some conceptual problems regarding the measurements. A quantitative analysis of the same data established that the bivariate relation was significant, with correlations of similar strength to those found for well‐established nonlinguistic predictors of language. Further exploration of infant speech perception predictors, particularly from a methodological perspective, is recommended.